2016
DOI: 10.15537/smj.2016.10.14998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GeneXpert MTB/RIF assay for direct diagnosis of pulmonary tuberculosis

Abstract: Objectives:To evaluate the performance of GeneXpert MTB/RIF assay for direct diagnosis of pulmonary tuberculosis (PTB).Methods:This is a cross-sectional study conducted between October 2013 and February 2016 at Abbassaia Chest Hospital and Ain Shams University Hospital, Cairo, Egypt. Inclusion criteria were adults between 18 and 60 years with suspected PTB and classified into 5 clinical categories based on their clinical, radiological, and laboratory findings: confirmed TB, probable TB, possible TB, unlikely T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…We considered 16 studies (19%) to have high risk of bias because the study did not avoid inappropriate exclusions: 13 studies enrolled participants whose sputum specimens were primarily or exclusively smear‐positive or smear‐negative (Barnard 2015; Friedrich 2011; Jo 2016; Lee 2013; Le Palud 2014; Meyer 2017; Mok 2016; Moure 2011; Tadesse 2016; Theron 2013; Van Rie 2013; Walusimbi 2013a; Williamson 2012) and three studies exclusively enrolled participants who had previously received tuberculosis treatment (Meawed 2016; Metcalfe 2015; Pimkina 2015). In addition, we considered 15 studies (17%) to have unclear risk of bias because the manner of participant selection was not stated (Atwebembeire 2016; Barmankulova 2015; Bates 2013a; Boum 2016; Chen 2017; Huang 2015; Kim CH 2015; Luetkemeyer 2016; Mbelele 2017; Moussa 2016; Mutingwende 2015; Nosova 2013a; Reechaipichitkul 2017; Shao 2017; Shenai 2016). With respect to applicability, we considered 46 studies (53%) to have low concern because participants in these studies were evaluated in primary care facilities, local hospitals, or both settings (Adelman 2015; Al‐Darraji 2013; Balcells 2012; Balcha 2014; Barmankulova 2015; Bjerrum 2016; Boehme 2010; Boehme 2011; Boum 2016; Calligaro 2017; Carriquiry 2012; Chen 2017; Dorman 2018; Friedrich 2011; Hanrahan 2013; Hanrahan 2014; Henostroza 2016; Huang 2015; Kurbaniyazova 2017; Kurbatova 2013; …”
Section: Resultsmentioning
confidence: 99%
“…We considered 16 studies (19%) to have high risk of bias because the study did not avoid inappropriate exclusions: 13 studies enrolled participants whose sputum specimens were primarily or exclusively smear‐positive or smear‐negative (Barnard 2015; Friedrich 2011; Jo 2016; Lee 2013; Le Palud 2014; Meyer 2017; Mok 2016; Moure 2011; Tadesse 2016; Theron 2013; Van Rie 2013; Walusimbi 2013a; Williamson 2012) and three studies exclusively enrolled participants who had previously received tuberculosis treatment (Meawed 2016; Metcalfe 2015; Pimkina 2015). In addition, we considered 15 studies (17%) to have unclear risk of bias because the manner of participant selection was not stated (Atwebembeire 2016; Barmankulova 2015; Bates 2013a; Boum 2016; Chen 2017; Huang 2015; Kim CH 2015; Luetkemeyer 2016; Mbelele 2017; Moussa 2016; Mutingwende 2015; Nosova 2013a; Reechaipichitkul 2017; Shao 2017; Shenai 2016). With respect to applicability, we considered 46 studies (53%) to have low concern because participants in these studies were evaluated in primary care facilities, local hospitals, or both settings (Adelman 2015; Al‐Darraji 2013; Balcells 2012; Balcha 2014; Barmankulova 2015; Bjerrum 2016; Boehme 2010; Boehme 2011; Boum 2016; Calligaro 2017; Carriquiry 2012; Chen 2017; Dorman 2018; Friedrich 2011; Hanrahan 2013; Hanrahan 2014; Henostroza 2016; Huang 2015; Kurbaniyazova 2017; Kurbatova 2013; …”
Section: Resultsmentioning
confidence: 99%
“…Moussa et al noted a similar finding about usage of GX in PTB. They suggested that it should not be used alone, as clinical and radiological assessments were still important components of the diagnosis pathway [20]. The added advantage of GX testing is evaluation of rifampicin resistance, which is the first line of drug in the management of TB.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, Moussa et al, 2016, found that the sensitivity and specificity of the GeneXpert assay were 93% and 98.3% respectively. This relatively low sensitivity compared to our results could be due to a low number of patients (218) and different study design.…”
Section: Resultsmentioning
confidence: 99%